2008
DOI: 10.15381/rpb.v15i2.1743
|View full text |Cite
|
Sign up to set email alerts
|

Ocurrencia de Ascaridia hermaphrodita (Nematode: Ascaridiidae) en el loro de Cabeza Azúl (Pionus menstruus) en Perú

Abstract: We report for first time the presence of nematode, Ascaridia hermaphrodita Froelich, 1789, parasiting small intestine of a Blue-Headed Parrot (Pionus menstruus Linnaeus, 1776). The specimen was sent to Avian Pathology Laboratory of Veterinary School of San Marcos University, Lima, Peru. Eighteen nematodes (12 females and 6 males) were studied and identified as A. hermaphrodita. The dicovery of this specie in P. menstruus is the first record in Perú.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…Hodová et al (2008) reported that five species of Ascaridia are frequent in Psittaciformes; A. platyceri and A. hermaphrodita are the most common. In Brazil, Pinto et al (1993) reported A. hermaphrodita as specific of psittacines of genuses Amazona, Anodorhynchus, Ara, Aratinga, Brotogeris, Conurus, Pyrrhura, Psittacus and Pionus; this fact corroborates studies on psittacines in Argentina, Chile and Peru (MARTÍNEZ et al, 2003;MASELLO et al, 2006;GONZÁLEZ-ACUÑA et al, 2007;GÓMEZ-PUERTA et al, 2008).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Hodová et al (2008) reported that five species of Ascaridia are frequent in Psittaciformes; A. platyceri and A. hermaphrodita are the most common. In Brazil, Pinto et al (1993) reported A. hermaphrodita as specific of psittacines of genuses Amazona, Anodorhynchus, Ara, Aratinga, Brotogeris, Conurus, Pyrrhura, Psittacus and Pionus; this fact corroborates studies on psittacines in Argentina, Chile and Peru (MARTÍNEZ et al, 2003;MASELLO et al, 2006;GONZÁLEZ-ACUÑA et al, 2007;GÓMEZ-PUERTA et al, 2008).…”
Section: Introductionsupporting
confidence: 53%
“…Parasitic infections are one of the major health problems of wild birds kept in captivity (RITCHIE et al, 1994;GÓMEZ-PUERTA et al, 2008;OLIVEIRA et al, 2011). Damage to the host and symptoms depend on the pathogenicity and intensity of infection and general condition of the animal (immune competence) (GODOY, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Blue-fronted parrots are frequently reported as hosts of A. hermaphrodita (5,9). In 36.4% of the necropsied Blue fronted parrots that presented ascaridiasis, low weight or cachexia was observed, in addition to the occurrence of secondary diseases due to the debility presented by the birds.…”
Section: Resultsmentioning
confidence: 99%
“…Infecções parasitárias são um dos principais problemas de saúde das aves silvestres mantidas sob cuidados humanos (Greiner e Ritchie, 1994;Gómez-Puerta et al, 2008;Oliveira et al, 2018). Existe uma variedade de helmintos que parasitam aves, sendo os principais grupos representantes os nematoides e cestoides (Rennó et al, 2008).…”
Section: Introductionunclassified